Climate change and water resources in the Bagmati River Basin, Nepal - Babel, Mukand S; Bhusal, Shyam P; Wahid, Shahriar M; Agarwal, Anshul (Theoretical and applied climatology, 2014)
This paper characterizes potential hydrological impact of future climate in the Bagmati River Basin, Nepal. For this research, basinwide future hydrology is simulated by using downscaled temperature and precipitation outputs from the Hadley Centre Coupled Model, version 3 (HadCM3), and the Hydrologic Engineering Center's Hydrologic Modeling System (HEC-HMS). It is predicted that temperature may rise maximally during the summer rather than winter for both A2 and B2 Special Report on Emissions Scenarios (SRES) scenarios. Precipitation may increase during the wet season, but it may decrease during other seasons for A2 scenario. For B2 scenario, precipitation may increase during all the seasons. Under the A2 scenario, premonsoon water availability may decrease more in the upper than the middle basin. During monsoons, both upper and middle basins show increased water availability. During the postmonsoon season, water availability may decrease in the upper part, while the middle part shows a mixed trend. Under the B2 scenario, water availability is expected to increase in the entire basin. The analysis of the projected hydrologic impact of climate change is expected to support informed decision-making for sustainable water management.